Synthesis, physico-chemical properties of derivatives 3-(alkylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-4-amine - A. A. Safonov (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Recently, the search for new compounds with high biological activity, which can be the basis for potential drugs, becomes topical for world scientists. A heterocyclic compound cause particular interest in this area as highly pharmacologically active compounds. Scientists extends interest due to the low toxicity and high reactivity 1,2,4-triazole of the system. It is proved that the combination of triazole nucleus with other heterocyclic systems, especially in the fifth position, causes increased biological effect, and, sometimes, the appearance of new pharmacological activities. The aim of the work was the synthesis of 3-(alkylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-4-amines and their derivatives, study of their physico-chemical properties. A series of new derivatives of the compounds 4-amino-5-R-1,2,4-triazole-3-thione (3-(alkylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-4-amines and N-R-idene)-3-(nonylthio)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-4-amines) was synthesizes. The structure of compounds is set with modern physico-chemical methods of analysis (elemental analysis, 1H-NMR spectroscopy). Individuality is proved by HPLC-MS.